Hermitage in Holland : Een tentoonstelling van Russische hedendaagse beeldende kunst. - Azar, August; Duk, Wierd; Loots, Ton; Malko, Sasza; Manche, Leopold; Michgelsen, Pauline; Prakken, Joanka; Sviblova, Olga; Zertsjaninov, Joerij; Studium Generale; Technische Universiteit, Eindhoven; Stichting Cultureel Buro Rusland "Circk", Amsterdam (Rotterdam : Stichting De Nieuwe Weelde, 1988)
Filatov, Nikolai ; Toernova, Gosja Ostretsov Natalja ; Rojter, Andrej ; Ostretsov, Georgij ; Petroek, Joery ; Sjoetov, Sergej ; Bordatsjov, Sergej ; Filatov, Kolja ; Tsykalov, Dimitri ; Vinogradov, Garik ; Soendoekov, Aleksej ; Volkov, Sergej ; Zjor, Sturman
Nederlands & Russisch
kunstcatalogus
Keywords: Rusland